Young beneficiaries' routes off benefits through labour market integration: the case of Germany - Brigitte Schels (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2011)
The study explores routes off benefits through labour market integration for young adults in Germany. Policies for young people are focused on a rapid integration into employment or training to prevent long-term benefits dependency. The causes of long-term benefits receipt can be related to poor labour market opportunities. But in political and public discourse, long-term benefits dependency is most widely regarded as the consequence of young adults' low labour supply. The article examines the labour market transitions of 650 beneficiaries aged 18 to 24. The analysis combines survey data on beneficiaries in Germany and longitudinal register data for 2005 to 2007. Though most of the young adults surveyed enter employment or vocational training, a high percentage continues to receive benefits. Long-term benefits receipt is related to low levels of qualifications and young parenthood; there is no evidence for young people resigning themselves to benefits receipt.
Keywords: I38; J64; C41; 330; arbeitslose Jugendliche; Arbeitslosengeld II-Empfänger; berufliche Integration; junge Erwachsene; Grundsicherung nach SGB II; Ausbildungsförderung; Beschäftigungsförderung; benachteiligte Jugendliche; Benachteiligtenförderung; erste Schwelle; zweite Schwelle; Leistungsbezug - Dauer